2012
DOI: 10.1124/jpet.111.188169
|View full text |Cite
|
Sign up to set email alerts
|

Immunophyllin Ligands Show Differential Effects on Alcohol Self-Administration in C57BL Mice

Abstract: High abstinence rates characterize alcohol-dependent liver graft recipients. The immunosuppressants cyclosporine A (CsA) and tacrolimus (TRL) also inhibit calcineurin (CLN) in the brain. Previously, we found that CsA reduces alcohol consumption in C57BL/6J mice. The goals of the present study were: 1) to compare the ethanol preference effects of CsA against TRL, as well as sirolimus (SRL), an immunosuppressant without CLN inhibition and 2) to establish that reduction of alcohol consumption is not caused by cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Tacrolimus, a calcineurin inhibitor, has been shown to reduce limited-access ethanol intake in male C57BL/6J mice. 28 Here, we examined whether tacrolimus would reduce binge-like ethanol intake in male and female HDID-1 mice. Experimental procedures are shown in Figure 1a .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Tacrolimus, a calcineurin inhibitor, has been shown to reduce limited-access ethanol intake in male C57BL/6J mice. 28 Here, we examined whether tacrolimus would reduce binge-like ethanol intake in male and female HDID-1 mice. Experimental procedures are shown in Figure 1a .…”
Section: Resultsmentioning
confidence: 99%
“…The presently used HDID-1 mice represent a unique, genetic risk model in which to screen the efficacy of promising neuroimmune and neuroinflammatory compounds. For the calcineurin inhibitor, tacrolimus, we were informed by the work of Beresford et al, 28 whereby 2.5 mg/kg of tacrolimus decreased 10% ethanol preference and intake in C75BL/6J male mice. Neasta et al 31 reported that systemic administration of the mTOR inhibitor, sirolimus (rapamycin), significantly reduced conditioned place preference to ethanol in DBA/2J male mice and reduced 20% ethanol intake in male C75BL/6J mice when given every other day, for 4 hours (beginning 2 hours into the dark cycle).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations